2020
DOI: 10.2337/dc20-0204
|View full text |Cite
|
Sign up to set email alerts
|

Association of Type 2 Diabetes With Cancer: A Meta-analysis With Bias Analysis for Unmeasured Confounding in 151 Cohorts Comprising 32 Million People

Abstract: BACKGROUND AND PURPOSEWhether the association between type 2 diabetes (T2D) and cancer is causal remains controversial. The goal of this work is to assess the robustness of the observational associations between T2D and cancer to unmeasured confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 47 publications
4
102
0
15
Order By: Relevance
“…A recent report involving a large population ( n = 112818 females and 46207 males respectively) over 30 years of cumulative exposure showed an increased risk of PDAC with long-standing diabetes over time (age-adjusted hazard ratio [HR] 2.16 [95%CI: 1.78-2.60])[ 11 ]. Another recently published meta-analysis also suggested an increased PC related mortality with T2DM (relative risk [RR] 1.67; [95%CI: 1.30-2.14])[ 12 ].…”
Section: Risk Of Pc In Long-standing Diabetes Mellitusmentioning
confidence: 99%
“…A recent report involving a large population ( n = 112818 females and 46207 males respectively) over 30 years of cumulative exposure showed an increased risk of PDAC with long-standing diabetes over time (age-adjusted hazard ratio [HR] 2.16 [95%CI: 1.78-2.60])[ 11 ]. Another recently published meta-analysis also suggested an increased PC related mortality with T2DM (relative risk [RR] 1.67; [95%CI: 1.30-2.14])[ 12 ].…”
Section: Risk Of Pc In Long-standing Diabetes Mellitusmentioning
confidence: 99%
“… 152 However, most of these activators are targeting components in canonical Wnt pathway rather than Wnts, and their efficacy and safety are only evaluated in cells or diseased animal models rather than in clinical trials. Furthermore, activation of canonical Wnt pathway may accelerate the progression of some diabetic complications, and diabetic patients have an increased risk of cancers due to the direct effect of hyperglycaemia and indirect effects of insulin resistance, hyperinsulinaemia and chronic inflammation, 155 , 156 and overactivation of canonical Wnt pathway serves as primary determinant for most human malignancies; hence, systemic application of Wnt activators on diabetic patients may aggravate certain diabetic complications or increase the risk of cancer incidence.…”
Section: Opportunities and Challenges In Developing Therapeutics For T2dm And Complications Based On Wntsmentioning
confidence: 99%
“…However, most of these activators are targeting components in canonical Wnt pathway rather than Wnts, and their efficacy and safety are only evaluated in cells or diseased animal models rather than in clinical trials. Furthermore, activation of canonical Wnt pathway may accelerate the progression of some diabetic complications, and diabetic patients have an increased risk of cancers due to the direct effect of hyperglycaemia and indirect effects of insulin resistance, hyperinsulinaemia and chronic inflammation,155,156 and overactivation of canonical Wnt pathway serves as primary determinant for most human malignancies; hence, systemic application of Wnt activators on diabetic patients may aggravate certain diabetic complications or increase the risk of cancer incidence.Compared with the conflicting role of canonical Wnt pathway, non-canonical Wnt pathways are consistently overactivated in diabetes and related complications, and the expression of related Wnts, including Wnt4, Wnt5a, Wnt5b and Wnt11, is increased in diseased tissues in diabetic environment. Therefore, inhibition of the non-canonical Wnt pathway is a promising therapeutic approach for the treatment obesity, T2DM and related complications.…”
mentioning
confidence: 99%
“…Given the results of these simple sensitivity analyses, we recommend that the metaanalyst then attempt to assess and report whether it is actually plausible that the metaanalyzed studies are subject to confounding as severe as that indicated by the E-values and by G(r, q). Examples can be found in existing meta-analyses (3,10,26). This assessment would be based on substantive knowledge of the exposures and outcomes under consideration and the ROB assessments described in Section 2.…”
Section: Overall Sensitivity Analysis Recommendationsmentioning
confidence: 99%